Passion and responsibility: The puzzle of asymmetry - Załuski Wojciech (Anali Pravnog Fakulteta u Beogradu, 2023)
To what extent - if at all - acting in passion diminishes the agent's responsibility for his/her deed? Some new aspects of this classical problem have been discovered by experimental psychologists (Pizarro, Uhlmann, Salovey) whose research has revealed a puzzling asymmetry in assigning responsibility for morally bad and morally good actions, performed under the influence of emotions (people tend to regard the blameworthiness of an immoral act as being diminished by the fact that it was performed in passion, but do not regard passion as influencing the praiseworthiness of a moral act). The article discusses the puzzle's explanation proposed by the authors of the experiment (based on the concept of "metadesires") and offers an alternative explanation, drawing on the distinction between passio antecedens and passio consequens, proposed by Thomas Aquinas. The paper also provides some reflections on the normative aspects of the problem of acting under the influence of emotions.